74 Safety and Feasibility of Day Case Cardiac Resynchronization Therapy Implantation – A Single Tertiary Centre Experience. (6th June 2015) - Ahmed, Nauman; Sun, Pheobe; Rajagopalan, Urjitha; Cripps, Tim; Thomas, Glyn; Duncan, Edward; Diab, Ihab
Abstract : Introduction: Cardiac resynchronisation therapy (CRT) is an established treatment for symptomatic heart failure. Most centres mandate an overnight hospital stay to monitor for any potential complications, mainly LV lead displacement. This increases pressure on beds and the costs of implantation. Due to increasing experience and better equipment, the LV lead displacement rate is currently low, with shorter procedures and reduced contrast use, which negates the need for overnight stays. The aim of this study is to assess feasibility, safety and patient acceptability of day case CRT implantation. Methods: We identified patients who underwent elective CRT implantation from September 2013 to March 2014 by two operators. These were done as planned day cases or planned overnight stays depending on operator preference. Patient demographics, procedure details, and complications were recorded for both groups. All patients were surveyed by telephone for their satisfaction with the procedure, hospital stay and discharge process. Results: We identified 53 patients during the study period of which 35 (66%) patients were planned as day case procedures. Out of these 35 patients, 22 (63%) were discharged the same day. 5 (14%) patients were kept overnight due to clinical reasons: 3 small haematomas and 1 coronary dissection for observation and 1 patient who felt generally unwell post procedure. All 5 patients were discharged the next day. The remaining 8 (23%) patients had to stay overnight due to non-clinical reasons: n = 5 due lack of home support or transport issues and n = 3 due late finish of implant procedure. Patients who were discharged the same day had no complications after discharge or during the first 6 weeks. Among the 18 (34%) planned overnight stay patients, 2 patients had RV lead displacements detected at 6 weeks follow-up that were not identified on next morning predischarge assessment or pacing check. All patients were contacted by telephone and 48 (90%) patients responded to the survey. The responses of patients who were initially planned as day case procedure but had to stay overnight (n = 13) were excluded to eliminate bias. Results are shown in the Table 1 below. Conclusion: Day case CRT implantation is feasible, safe and is preferred by the majority of patients particularly those who have received a day case implant. Overnight night stay post implantation appears unnecessary. Unplanned overnight stays for non-clinical reasons can be avoided with better planning of cath lab schedules and logistics.